Pengaruh Penggunaan Media Audio Visual Terhadap Prestasi Belajar Siswa dalam Pembelajaran Matematika - Ilyas Rifa’i; Uus Sopandi; Erni Kusmiat; Santi Nurpinawati (STAI Siliwangi Bandung, 2022)
This study aims to determine the effect of the use of audio-visual media on the learning achievement of fourth-grade students in learning mathematics at MI Tembongsari Cihampelas. The method used in this research is an experimental method with a one-group pretest-posttest design. Data collection techniques used include observation, testing, and documentation. While the data analysis technique used is the analysis of observation results, the N-Gain test, and the T-Test test. The results of this study indicate that the use of audio-visual media significantly affects student achievement in learning mathematics. Through the N-Gain test, the results obtained were 0.67 with a percentage of 67%, which was interpreted as quite effective, and through the T-test, the t-count results were greater than the t-table (24.75 > 2.035). This result means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, namely that there is a positive effect of the use of audio-visual media on student achievement in learning mathematics in class IV MI Tembongsari Cihampelas.